Influence of fissure integrity on quantitative CT and emphysema distribution in emphysema-type COPD using a dedicated COPD software - Müller, Jan; Lim, Hyun-ju; Eichinger, Monika; Jobst, Bertram; Eberhardt, Ralf; Gompelmann, Daniela; Puderbach, Michael; Kauczor, Hans-Ulrich; Heußel, Claus Peter; Wielpütz, Mark Oliver (European journal of radiology, 2017)
Objectives Fissure integrity (FI) plays a key role in selecting patients for interventional emphysema therapy. We investigated its interference with automated lobar segmentation in quantitative computed tomography (CT) and emphysema distribution. Methods CT was available for 50 patients with chronic obstructive pulmonary disease (COPD). Lobe segmentation was performed fully automated by software and corrected manually. FI was evaluated visually using a %-scale. The influence of FI on emphysema ratio (ER=percentage of lung volume with density values<−950 HU), mean lung density (MLD), emphysema and total volume of adjacent lobes was analyzed. Lobe-based results were compared with respect to FI. Results Differences in ER in adjacent lobes for complete vs. incomplete fissures were 12.4% for the right horizontal, 0.2% and 3% for the right oblique and 4.4% for the left oblique fissure (all p>0.05). Results for emphysema comparing automated vs. manually corrected segmentation exceeded clinically acceptable values, but were not significantly affected by FI (p>0.05). The widest limits of agreement for ER and MLD were noted in the right middle lobe ([−14, 17.4%], [−22.4, 32.4 Hounsfield Units]). Conclusions Automated lobe segmentation and emphysema distribution are not significantly affected by FI. Manual correction of automated lobar segmentation is still recommended in severe emphysema.
Gesehen am 30.05.2018